2021
DOI: 10.3390/molecules26061567
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Inhibits Expression of Matrix Metalloproteinase-10 and Invasion in Helicobacter pylori-Infected Gastric Epithelial Cells

Abstract: Matrix metalloproteinases (MMPs), key molecules of cancer invasion and metastasis, degrade the extracellular matrix and cell–cell adhesion molecules. MMP-10 plays a crucial role in Helicobacter pylori-induced cell-invasion. The mitogen-activated protein kinase (MAPK) signaling pathway, which activates activator protein-1 (AP-1), is known to mediate MMP expression. Infection with H. pylori, a Gram-negative bacterium, is associated with gastric cancer development. A toxic factor induced by H. pylori infection is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…MMP-10 is an important member of MMPs. MMP-10 was anomalously expressed in numerous tumors, such as gastric cancer [ 11 ], esophageal cancer [ 12 ], and head and neck cancer [ 13 ]. MMP-10 is a protease closely related to tumor invasion and metastasis, whose main function is to degrade extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-10 is an important member of MMPs. MMP-10 was anomalously expressed in numerous tumors, such as gastric cancer [ 11 ], esophageal cancer [ 12 ], and head and neck cancer [ 13 ]. MMP-10 is a protease closely related to tumor invasion and metastasis, whose main function is to degrade extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, ROS affects cell signal transduction and causes gastric cancer. erefore, eliminating ROS levels in H. pylori-infected cells may prevent worsening the disease [23]. Our functional experiments revealed that CN reduced the production of ROS in GSE-1 cells caused by H. pylori infection in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 66%
“…In our study, we found that MMP10 was activated under conditions of oxidative stress in the RPE. In this regard, it has been shown that reducing intracellular oxidative stress, both by transfecting cells with a physiological redox regulator [ 34 ] and by adding an antioxidant [ 35 ], β-Carotene, reduces MMP10 expression in cells. Based on these findings, it can be speculated that MMP10 may have either a beneficial role in facilitating the recycling of the BM in situations where its deterioration increases cellular stress or a deleterious role in facilitating the sprouting vessels to cross the membrane.…”
Section: Discussionmentioning
confidence: 99%